Scottish criminal evidence law : current developments and future trends / edited by Peter Duff, Professor of Criminal Justice, University of Aberdeen, and Pamela R Ferguson, Professor of Scots Law, University of Dande. - Duff, Peter, 1954-; Ferguson, Pamela R. (Edinburgh University Press, 2018)
This book gathers leading experts in the field to analyse the recent, major changes in Scots criminal evidence law. The areas affected include: police questioning of suspects, the treatment of vulnerable witnesses in court, hearsay, the admissibility of the accused's previous convictions, the Crown's duty of disclosure and corroboration.